Hölderlin's Sapphic mode - Menninghaus, Winfried (Primerjalna književnost, 2006)
Revising the notion of Hölderlin the Pindaric prophet-poet, the essay presents a Sapphic counterpart in Hölderlin's poetry, and highlights the outstanding significance of Sappho for both the theory of lyrical poetry, gender politics, and the notion of symbolic female authority around 1800.
Keywords: Hölderlin, Friedrich, 1770-1843; nemška poezija; literarni vplivi; Sapfo